Comparative Analysis of Different Extracellular Matrices for the Maintenance of Bovine Satellite Cells - Jae Ho Han; Si Won Jang; Ye Rim Kim; Ga Rim Na; Ji Hoon Park; Hyun Woo Choi (Animals)
Cultured meat produced using satellite cells has emerged to address issues such as overpopulation, the ethical conundrums associated with the breeding environment, and the methane gas emissions associated with factory farming. To date, however, the challenges of maintaining satellite cells in vitro and reducing the costs of the culture media are still substantial. Gelatin, collagen, and fibronectin are commonly used extracellular matrices (ECMs) that facilitate signal integration with the cells and promote cell adhesion. In this study, we compared the proliferation, cell cycle, immunocytochemistry, and expression levels of Pax7, Pax3, Myf5, MyoD1, and MyoG genes in bovine satellite cells (BSCs) cultured on gelatin-, collagen- and fibronectin-coated dishes as part of short- and long-term cultures. We observed that BSCs cultured on gelatin-coated dishes showed higher levels of Pax7 expression than BSCs cultured on collagen- and fibronectin-coated dishes in both short- and long-term cultures, indicating that BSCs cultured on gelatin effectively maintained the satellite cell population in both the short- and long-term cultures. Our study highlights that gelatin is an effective ECM for the maintenance of BSCs and the production of cultured meat.